Are there differences in the quality of the diet of working and stay-at-home women? - Assumpção, Daniela de; Senicato, Caroline; Fisberg, Regina Mara; Canesqui, Ana Maria; Barros, Marilisa Berti de Azevedo (Revista de Saúde Pública, 2018)
OBJECTIVE: To verify whether there is an association between the quality of the diet and the inclusion of women in the labor market and whether the education level would modify this association. We have analyzed the differences according to education level and evaluated whether the insertion or not in the market modifies the association between the quality of the diet and education level. METHODS: This is a cross-sectional population-based study that has used data from the Campinas Health Survey (2008 ISACamp). We have evaluated the diet of 464 women, aged 18 to 64 years, using the Brazilian Healthy Eating Index – Revised. We have estimated the means of the total score and index components using simple and multiple linear regression. RESULTS: We have observed no difference in the quality of diet of working and stay-at-home women. The analysis stratified by education level showed a lower intake of fruits among stay-at-home women in the segment of lower education level, in relation to working women. Among all women, a lower education level was associated with lower overall quality of the diet, higher intake of sodium, and lower intake of fruits, vegetables, whole grains, milk, and saturated fat. On the other hand, the inclusion in the labor market changed the effect of the education level on the quality of the diet. In the stay-at-home stratum, a low education level was associated with poorer quality of the diet and lower consumption of fruits, dark green and orange vegetables, and whole grains. Among the working women, a low education level was associated with higher intake of sodium and lower intake of vegetables, whole grains, and milk and dairy products. CONCLUSIONS: The results show inequities in the profile of food in relation to education level and inclusion in the labor market, which shows the relevance of public policies that increase the access to education and provide guidance on a healthy diet.